2021
DOI: 10.1007/s13278-021-00790-8
|View full text |Cite
|
Sign up to set email alerts
|

Mining brand value propositions on Twitter: exploring the link between marketer-generated content and eWOM outcomes

Abstract: Content marketing has become a mainstream channel for brands to engage the market with value propositions. Through content, brands control, instigate and co-create value with its target audience. However, the nature of value propositions embedded within the cycle of content co-creation and their impact on eWOM outcomes has received scant attention from an empirical perspective. In this paper, we propose a value proposition-based framework around content marketing using established business perspectives. We emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 97 publications
0
11
0
Order By: Relevance
“…In the process of participating in a brand community, community members are constantly exposed to other consumers sharing brand stories and helping other consumers use the brand ( Laroche et al, 2012 ), which invariably strengthens community participants’ shared love for the brand and a common community identity, which provides important conditions for forming a community identity ( Song, 2015 ); at the same time, participation in community interactions is accompanied by the establishment of relationships among community members, and the establishment of community member relationships leads to the creation of reciprocal norms and a sense of shared responsibility in the community similar to those in real interactions ( Laroche et al, 2012 ), which makes community members take the initiative to assume certain roles in the community (e.g., community manager, etc.) to help the community, and this relational community embedding can facilitate consumers to form an identity with the community ( Alwash et al, 2021 ). Therefore, community identity has a mediating role between interactive experience and brand identity.…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%
“…In the process of participating in a brand community, community members are constantly exposed to other consumers sharing brand stories and helping other consumers use the brand ( Laroche et al, 2012 ), which invariably strengthens community participants’ shared love for the brand and a common community identity, which provides important conditions for forming a community identity ( Song, 2015 ); at the same time, participation in community interactions is accompanied by the establishment of relationships among community members, and the establishment of community member relationships leads to the creation of reciprocal norms and a sense of shared responsibility in the community similar to those in real interactions ( Laroche et al, 2012 ), which makes community members take the initiative to assume certain roles in the community (e.g., community manager, etc.) to help the community, and this relational community embedding can facilitate consumers to form an identity with the community ( Alwash et al, 2021 ). Therefore, community identity has a mediating role between interactive experience and brand identity.…”
Section: Theoretical Foundation and Hypothesis Developmentmentioning
confidence: 99%
“…Lagun and Lalmas ( 25 ) used taxonomy to divide user engagement into four levels, i.e., bounce, shallow, deep, and complete. Aroused by Lagun's taxonomy and COBRAs framework, Alwash et al ( 6 ) propose two levels of user engagement with brand value propositions—shallow and deep user engagement.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have shown that more than 90% of patients only browse the website without any further engagement behavior ( 5 ). Broadly, user engagement behavior can be viewed at two levels, namely shallow engagement and deep engagement ( 6 ). In the context of OHCs, patient engagement behavior for medical services includes two steps, visiting physicians' home page (i.e., patient visit) and purchase consultation services (i.e., patient consultation), which correspond to these two levels of engagement.…”
Section: Introductionmentioning
confidence: 99%
“…In some previous studies, buying decisions were associated with marketing mix variables (see also Kotler & Keller, 2016) such as product, price, place, and promotion (see also Alwash et al, 2021;Kovač et al, 2021;Kung et al, 2021). In online purchases, there are risks and uncertainties when shopping, so there are other factors to consider, namely the quality of the web.…”
Section: Introductionmentioning
confidence: 99%